HUBUNGAN LAMA DAN SIKAP DUDUK TERHADAP KEJADIAN NYERI PADA PUNGGUNG BAWAH MAHASISWA - Kamarulzaman " "; Bayhakki " "; Misrawati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research was to identify the correlation between length and sitting position to complaints of low back pain of students. Research method used in the study was descriptive correlational with cross sectional approach. The sampling technique used was stratified random sampling with 176 respondents which were selected based on inclusion criteria. This research used questionnaire for variable length and sitting position and physical examination sheet for complaint of low back pain. The univariate analysis was done by using distributions of frequencies and bivariate analysis was done by using chi-square test. The result showed that, there was no correlation length to complaints of low back pain (p value 0.619 > α 0.05) and there was the correlation between sitting position to complaints of low back pain (p value 0.000 < α 0.05). According to this research,  it is necessary for students to pay attention to sitting position for a long time in order to prevent the occurrence of lower back pain. Keywords: Length and sitting position, low back pain, student